Identificação das condições gerais de conservação dos reservatórios integrantes do sistema de abastecimento de água de Natal - Pereira, Hazen Willian Bezerra (2014)
Infrastructure works are included in strategic areas for the social development. For that matter that all of the investments are very important for the social development. When the population has enough water and an acceptable quality, and it includes a wastewater gathering and its treatment, the whole society became less susceptible to the water diseases. Even the Water Supply and the Sewage depend for its perfect operation of reservoirs, or of the accumulation of water to provide the popular necessity, either due to retention or for the treatment wastewarer. These structures present very specific environmental conditions, because the microclimate created around them, like high environmental humidity and for the existence of many harmful substances for the concrete, such as chloride ions presents in water. The reservoir that compose the System of Water Supply of Natal were built between 1970s and 1980s, a period whom the technical and scientific community did not have in-depth studies about the reinforced concrete mechanism of deterioration. Therefore, these reservoirs have been suffered accelerated deterioration progress, and they have been shown many pathological manifestations strikingly visible. In front of all these problems this academic work aims to identify the generally conditions of conservation of all the reservoirs components of the Water Supply System of Natal. This academic work objectives to develop a recuperation plan for use in these reservoirs, in this academic work it was achieved all the survey of pathological manifestation existing in each reservoir. It was made with local visits, photographic recorders of all manifestations viii and realization of in loco tests. The other step consisted in a application of GDE/UnB metodolgy reformulated by Fonseca (2007). In the step of local visits in each reservoir it was evaluated carbonation depth, by spreading a phenolphthalein solution with 1% of concentration; evaluation of contamination of chlorides, by spreading silver nitrate solution with 1% of concentration, and evaluation of width cracks. After the conclusion of all the testings, it was established that all reservoir, studied in this academic work, have showed an advanced deteriorating condition. It´s presents prevalent pathological manifestations as unacceptable cracks, spots, efflorescence and reinforcement corrosion, and in some cases, chlorides contamination. After the conclusion of the testings and its concatenation it was able to implementing, using GDE/UnB methodology, the order of the restoration its service life and initial safety conditions